1998
DOI: 10.1046/j.1365-2249.1998.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL-13 in IgE synthesis by allergic asthma patients

Abstract: SUMMARYIgE antibodies play a crucial role in allergic type I reactions. Only IL-4 and IL-13 are able to induce an immunoglobulin isotype switch to IgE in B cells. A major question is to what extent these cytokines contribute to the production of IgE in allergic patients. To address this question we used an in vitro culture system in which the production of IgE is dependent on endogenously produced IL-4 and IL-13. In cultures of purified T and B cells from allergic asthma patients and non-atopic controls, T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 47 publications
1
55
0
1
Order By: Relevance
“…Furthermore, IL-13 expression and IL-13 gene polymorphisms have been found to associate with increased IgE expression in atopic patients (5,28). A direct role for IL-13 in regulating lung epithelial cell function has also been reported, indicating that IL-13 may differentially modulate subsets of lung fibroblasts, inducing recruitment and activation of inflammatory cells (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, IL-13 expression and IL-13 gene polymorphisms have been found to associate with increased IgE expression in atopic patients (5,28). A direct role for IL-13 in regulating lung epithelial cell function has also been reported, indicating that IL-13 may differentially modulate subsets of lung fibroblasts, inducing recruitment and activation of inflammatory cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and immunological analyses of atopic individuals have revealed that Th2-type cytokines are causally associated with atopy (2,4). Recently, elevated levels of IL-13 have been found to correlate with IgE and atopy in allergic asthma patients (5), and a search for genetic variants of the IL-13 gene and its signaling components has emphasized an important role for this cytokine in asthma and atopy (6). Experimental mouse models have also highlighted the importance of IL-13 in immune responses and atopy.…”
mentioning
confidence: 99%
“…In asthma, Th2-related cytokines such as IL-4 [3537], IL-5 [38], and IL-13 [35,37] significantly increase; the development of antibodies against Th2-related cytokines is an active field of research [39]. Changes in Th17 cells correlate with asthma induction, making it important to analyze Th-17 proteins such as TNF-α, IL-6, and IL-1β [40].…”
Section: Discussionmentioning
confidence: 99%
“…In macrophages, PGE2 down-regulates the expression of MHC class II antigens (10), inhibits the production of IL-1 (11), IL-12 (12,13), TNF-α (14), and superoxide (15) and increases IL-10 production in response to LPS (12,16). This pattern of cytokine release by APCs favors the differentiation of naive T cells towards a Th2 phenotype and promotes B lymphocyte isotype switching to IgE.…”
Section: Pge2 In Transplantationmentioning
confidence: 99%